The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1111/bcp.12433
|View full text |Cite
|
Sign up to set email alerts
|

Determination of optimal vitamin D3 dosing regimens in HIV‐infected paediatric patients using a population pharmacokinetic approach

Abstract: AIMSTo investigate D] population pharmacokinetics in children and adolescents, to establish factors that influence 25(OH)D pharmacokinetics and to assess different vitamin D3 dosing schemes to reach sufficient 25(OH)D concentrations (>30 ng ml −1 ). METHODSThis monocentric prospective study included 91 young HIV-infected patients aged 3 to 24 years. Patients received a 100 000 IU vitamin D3 supplementation. A total of 171 25(OH)D concentrations were used to perform a population pharmacokinetic analysis. RESULT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 33 publications
(52 reference statements)
1
10
1
Order By: Relevance
“…In our study, a notable difference with previous studies is the large between-subject variability in 25(OH)D clearance. Compared to other studies which have also reported high between-subject variability (60-65%) despite a relatively homogeneous population, [19][20][21] our finding of 94% is likely to reflect an even more heterogenous cohort of patients with respect to 25(OH)D clearance. Although no covariate was identified as significant in our study, there is a strong biological plausibility that clearance could be affected in subjects with primary glomerular disease; our cohort included 20 children with glomerular disease, who compared to those with nonglomerular disease, required clearance may differ by race.…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…In our study, a notable difference with previous studies is the large between-subject variability in 25(OH)D clearance. Compared to other studies which have also reported high between-subject variability (60-65%) despite a relatively homogeneous population, [19][20][21] our finding of 94% is likely to reflect an even more heterogenous cohort of patients with respect to 25(OH)D clearance. Although no covariate was identified as significant in our study, there is a strong biological plausibility that clearance could be affected in subjects with primary glomerular disease; our cohort included 20 children with glomerular disease, who compared to those with nonglomerular disease, required clearance may differ by race.…”
Section: Discussioncontrasting
confidence: 94%
“…We have developed the first population PK model of oral colecalciferol using data from an randomised controlled trial in children The high volume of distribution estimate in our study is perhaps to be expected given colecalciferol and 25(OH)D are both lipophilic molecules, but our estimated value is higher than those reported by Foissac et al and in other adult studies. [19][20][21] The differences in volume of distribution may be explained by differences in body composition of the study populations and/or differences in 25(OH)D protein binding. We acknowledge that there were insufficient data in our study to fully quantify a 2-compartment model that may better describe the tissue distribution of colecalciferol and 25(OH)D. Earlier studies, although limited, have pointed to a biphasic distribution, [35][36][37] and a 2-compartment population PK model of colecalciferol has been described in only 1 meta-analysis consisting of >5000 adult subjects.…”
Section: Discussionmentioning
confidence: 99%
“…With the exception of one Hepatitis C co-infected individual in the Foissac et al . [ 69 ] study, participants had no concomitant acute and/or chronic disease, apart from HIV. There were no patients noted to have concurrent TB.…”
Section: Resultsmentioning
confidence: 99%
“…Higher mean monthly 25OHD values were seen with higher doses of cholecalciferol [ 55 ]. Lower baseline values of 25OHD negatively impacted final serum 25OHD concentrations, and extended the time needed to reach 25OHD >50 nmol/L and 75 nmol/L [ 66 , 69 ]. Without supplementation, dietary intake of cholecalciferol, noted to be between 90–425 IU/day, was insufficient in achieving 25OHD >75 nmol/L.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation